Using assistive technologies to facilitate play by children with motor impairments: a methodological proposal. - Besio S (Technology & Disability, 2004)
The results are presented of the SIVA research project 'Technical Aids and Methodologies to facilitate Play by Children with Motor Impairments' (2000-2003).The project has been launched with the scope of improving learning of children with motor impairment by letting them directly interact with their environment through play. For the 6 children belonging to the study group individualised solutions to access play and toys have been studied and experimented. An on-purpose playroom has been equipped with the needed technological solutions; individualised educational programs have been developed and fulfilled.The planning of the project as well as its results are here discussed within the methodological framework of Action-Research.